Organizational Behavior. - Robbins, Stephen P., 1943-; Judge, Tim (Timothy Allan), ....- (Harlow : Pearson, 2022)
Robbins's Organizational Behavior continues to set the standard for textbooks in the discipline, making current, relevant topics come alive through an angaging writing style, cutting-edge content, and intuitive pedagogy. For over four deades, this book has been hailed for its balanced, discerning perspective on the most importent current issues facing organizations, managers, and employees. Thoroughly revised to include the most current business events and research in organizational behavior worldwide, this Updated Eighteenth Edition also includes a range of features that will strengthen students' understanding of the subject and prepare them for their future careers.
Keywords: Theory and practice of organization